Influence of polarization of free-electron system in semiconductor on the position of minimum in plasma light reflection - Severin, V.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
The dielectric permeability of the free-electron system in semiconductor is usually considered using the Drude-Lorentz model without taking into account this system polarization. But it seems reasonable to include polarization phenomena into consideration of the free-electron system behavior. In this paper, the position of minimum in plasma optical reflection by the system of free electrons is analyzed with allowance for this system polarization. This position can substantially differ from that given via calculation of it within the framework of the traditional Drude-Lorentz model. This difference is significant when analyzing the available experimental results.